Personal digital assistants as a mobile inspection system at construction site - Ong, Boon Thai (2006)
Construction defects are always the key concern of the construction industry. Different constructed facilities generate different types of defects and demanded different levels and types of quality, depending on the functions, system types, an, materials used. Nevertheless, construction projects was typically take place in an environment where it is difficult to gain access to conventional computers for use as real-time decision aids as gone through the project quality inspection. The objectives of this study was to identify the inspection process and standard check list used in practice at construction site; to identify the potential and requirement for mobile inspection system at construction site and to develop a prototype of a mobile inspection system for construction site. Data was gathered from the literature study and also through local construction organizations by means of interview questionnaire. A prototype was developed using rapid prototyping method in a final phase. The finding revealed that generally construction industry does not have its standard inspection process and standard check list in practice. Besides this, the study also reveals that there was a potential and requirement for mobile inspection system at construction site. Finally a mobile defect inspection which consists of a sub system checklist and reference system was developed to suit the need of industry. The developed prototype will standardize the way of managing building defects and improve quality, increased productivity of inspectors, accurate photographic records and improved building defect communication.